PENGARUH E-WORD OF MOUTH, KEPERCAYAAN MEREK, DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PENGGUNAAN E-COMMERCE SHOPEE DI KOTA DENPASAR - Ni Nyoman Wida Sugiantari; I Nengah Suardhika; I Gede Rihayana (VALUES, 2024)
A new shopping trend thas has emerged among today’s society is shopping online, especially after the emergence of many electronic commerce or what we usually know as e-commerce. The decision to use can be interpreted as choosing from two or more existing alternatives and choosing one of them, where the alternative choice that consumers choose depends on their needs which can encourage them to make the right choice, such as choosing to use e-commerce Shopee. This research aims to find out and explain E-Word of Mouth, Brand Trust, and E-Service Quality on Usage Decisions. The sample in this research was 96 respondents who were e-commerce Shopee users in Denpasar City. Determining the sample in this research used a non-probability sampling technique using purposive sampling. The analytical method used is multiple linear analysis. The research results show that E-Word of Mouth, Brand Trust, and E-Service Quality have a positive and significant effect on Usage Decisions.